Investigation of the structural and electrical properties of CdO/(Bi, Pb)−2212 superconducting phase. (1st June 2022) - Basma, H; Abbas, S; Labban, W; Awad, R; Matar, M
Abstract: This investigation reports the effect of the addition of CdO nanoparticles on the (Bi, Pb)−2212 superconducting phase. The superconducting samples of general formula (CdO)x Bi1.6 Pb0.4 Sr1.9 Ca1.1 Cu2.1 O8 (x = 0.00, 0.01, 0.02, 0.05, and 0.1 wt%) are synthesized using the conventional solid-state reaction technique. Powder x-ray diffraction analysis confirms the formation of a single-phase orthorhombic Bi-2212. The variations in the lattice parameters are explained based on the Jahn Teller distortion induced by the increase in the oxygen content owing to the addition of the CdO nanoparticles. The increase in the oxygen content is confirmed via idiomatic titration analysis. The grain morphology is investigated using scanning electron microscopy (SEM). The effect of CdO addition in enhancing grains connectivity by the filing of pores and voids is revealed. Fourier transform infrared (FTIR) spectroscopy is conducted to analyze the functional groups, based on the effect of calcination temperature and CdO addition. Dc-electrical resistivity measurements and I-V characteristics show an enhancement of the superconducting transition temperature (Tc ) and the critical current density (Jc ) with CdO addition up to x = 0.05 wt%, followed by a further decrease. By analyzing the results of the x-ray photoelectron spectroscopy (XPS), the variations of the superconducting properties are explained based on the preferred substitution of Pb 2+ ions in the Bi 3+ or Cu 2+ sites induced by the variations in the oxygen content generated by the addition of CdO nanoparticles.